Improving Students Soft Skills Using Thinking Process Profile Based On Personality Types - M.J. Dewiyani Sunarto (Institute of Advanced Engineering and Science, 2015)
The challenge in education field these days rises as the cause of society’s expectation for higher education. This increasingly complex expectation demands that higher education prepares the students to gain integrity. Higher education provides not only hard skills for the student, but also soft skills. By observing the hard skills side, Dewiyani [1] discovers a learning method based on cognitive process that is classified by personality types. This finding is proved to be effective in enabling students to solve problems. By utilizing the finding as well as employing qualitative and development methods, this research serves a purpose of developing learning method that can improving students’ soft skills attributes based on personality types. This leads to the conclusion that the cognitive process will also have the same influence on personal and interpersonal behaviors. The findings gained from this research demonstrate that soft skills attribute showed by every personality is various and it can be improved through the application of learning models that put forward cognitive process based of personality type classification. According to the gained findings, it is recommended that this learning model can be expanded to cover other subjects in higher education syllabus